2022
DOI: 10.3389/fpubh.2022.825874
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits and Barriers to Chinese COVID-19 Vaccine Uptake Among Young Adults in China

Abstract: Survey-based research has provided us with breadth regarding perceived benefits and barriers to COVID-19 vaccination among Chinese people. Most such research has been conducted within hypothetical COVID-19 vaccine contexts, and few studies are specific to young adults aged 18–40, a pivotal target population for COVID-19 vaccination. Now that the Sinopharm and Sinovac COVID-19 vaccines have been conditionally approved in China, qualitative investigation of young adults' perceptions of benefits and barriers to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Whether or not to vaccinate is one of the typical health behaviors of people in modern society, and the HBM has been widely used in relevant research, such as influenza vaccination [20,21], HPV (human papillomavirus) vaccination [22,23], and parents' willingness to vaccinate their children [24][25][26][27]. Since the outbreak of the COVID-19 pandemic, the HBM has been used to predict the public's vaccination intentions against COVID-19 [28][29][30][31][32][33][34]. Additionally, another study explored the public's attitude towards vaccination on the basis of the HBM [35].…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not to vaccinate is one of the typical health behaviors of people in modern society, and the HBM has been widely used in relevant research, such as influenza vaccination [20,21], HPV (human papillomavirus) vaccination [22,23], and parents' willingness to vaccinate their children [24][25][26][27]. Since the outbreak of the COVID-19 pandemic, the HBM has been used to predict the public's vaccination intentions against COVID-19 [28][29][30][31][32][33][34]. Additionally, another study explored the public's attitude towards vaccination on the basis of the HBM [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, our study suggests otherwise. In fact, recent studies indicate that positive attitudes towards TCM’s role in combating the COVID-19 pandemic are positively associated with nationalist, patriotic, or collectivist sentiments and values ( 44 46 ). In other words, TCM supporters in China are more inclined to trust the government and national medical system, unlike CAM users elsewhere who resist vaccines due to institutional dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Among awareness determinants, the present study found that the awareness of physical suitability for vaccination was associated with vaccine uptake. To some degree, worries over one's physical suitability for vaccination are relevant to their physical constitution or previous medical experiences ( 53 ). Previous research has shown that concerns about vaccines being inadequate for one's physical condition may cause vaccine rejection ( 54 ).…”
Section: Discussionmentioning
confidence: 99%